2010
DOI: 10.1254/jphs.10r01cr
|View full text |Cite
|
Sign up to set email alerts
|

NOX/NADPH Oxidase, the Superoxide-Generating Enzyme: Its Transcriptional Regulation and Physiological Roles

Abstract: Abstract. NADPH oxidase is a superoxide (O 2− )-generating enzyme first identified in phagocytes that shows bactericidal activities. It has been reported that O 2 − is also produced in an NADPHdependent manner in non-phagocytes. In the last decade, non-phagocyte-type NADPH oxidases have been identified, and the catalytic subunit NOX family has been found to be composed of five homologs, NOX1 to NOX5, and two related enzymes, DUOX1 and DUOX2. These NOX proteins have distinct features in dependency on other comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 101 publications
1
74
1
Order By: Relevance
“…In particular, angiotensin II is known to upregulate NADPH oxidase subunits and is commonly upregulated in renal injuries. 30 In addition, it was previously demonstrated that superoxide itself leads to the upregulation of NADPH oxidase in the renal cortex, 31 and that EC-SOD KO mice have increased NADPH activity and subunit expression. 32 The loss of EC-SOD could therefore increase superoxide, leading to a feed-forward mechanism in which NADPH oxidase is further upregulated.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, angiotensin II is known to upregulate NADPH oxidase subunits and is commonly upregulated in renal injuries. 30 In addition, it was previously demonstrated that superoxide itself leads to the upregulation of NADPH oxidase in the renal cortex, 31 and that EC-SOD KO mice have increased NADPH activity and subunit expression. 32 The loss of EC-SOD could therefore increase superoxide, leading to a feed-forward mechanism in which NADPH oxidase is further upregulated.…”
Section: Discussionmentioning
confidence: 98%
“…The NADPH oxidase subunits; p67 phox , p47 phox , NOXO1, p22 phox , NOX4 and DUOX2 are expressed in NIH3T3 cells [99]. However, only NOX4 and p22 phox have been proven sufficient for generation of ROS [99,102], and are therefore proposed to constitute the volume-sensitive NADPH oxidase in NIH3T3 cells [99], reducing but not excluding a potential role of CK2 regulation of NOX4 though p47 phox in these cells. On the other hand, inhibition of CK2 was demonstrated to increase the production of H 2 O 2 as a result of induced apoptosis [111].…”
Section: Taurine Release Regulation Of the Swelling Induced Signallimentioning
confidence: 99%
“…The effect of LPA and PMA on taurine transport is impaired in the presence of an NADPH oxidase inhibitor [99,101], i.e., PKC and LPA interferes at a step upstream to generation of ROS. NADPH oxidases generates superoxides which are converted by dismutation to the lipid permeable H 2 O 2 se (see [102]). Increased availability of H 2 O 2 leads to activation of tyrosine kinases and reduced phosphatase activity caused by oxidation of the thiol residue at an essential cysteine in the active site [103].…”
Section: Taurine Release Regulation Of the Swelling Induced Signallimentioning
confidence: 99%
“…NOX4-dependent H 2 O 2 generation seems to be required for myofibroblast differentiation, synthesis of ECM proteins, and contractility mediated by TGF-b1. Moreover, in murine models of lung injury, genetic or pharmacologic targeting of NOX4 attenuated fibrogenesis (3,65,76).…”
Section: Nox4mentioning
confidence: 99%